Bacterial growth in various muscle relaxants - Erhan, O.L.; Kilic, S.S.; Yasar, M.A.; Felek, S.; Onal, S.A.; Bestas, A. (My University, 1994)
Recently, bacterial growth in hypnotic drugs has been studied and noted that there were significant amount of bacterial growth in leftover drug solutions. In this study a similar investigation was carried out in muscle relaxants which are routinly used in intensive care and anaesthesiology units. For this purpose, 1.0 ml samples from succinylcholine, pancuronium, atracurium and vecuronium (4 mg, 10 mg) were taken at 0, 1, 6 and 24 hours after opening of the vials and bacterial species (Staph. epidermidis, E. coli, Corynebacterium diphteriae and Klebsiella) were added into the drugs. Afterwards, the drugs were inoculated into the bacterial growth media and colonies were counted in 24 hours. As a general result, there was a reduction in the number of bacterial colonies in the presence of drugs. There was no bacterial growth in vecuronium group. In the succinylcholine and atracurium groups at 6th hour, coagulase positive staphylococcus and Corynebacterium diphteriae growth were noted. These results might indicate that the leftover solutions of succinylcholine and atracurium should not be utilized after 6 hr of bottle/ampule opening.
DEGISIK KAS GEVSETICILERINDE BAKTERI UREMESI
Keywords: Bacterial growth; Contamination in anaesthesia; Muscle relaxant